Beethoven: The Sonatas for Piano and Violin. Thoughts on Their Interpretation - Rostal, Max (Munich Toccata, 1985)
This book is the first in over half a century to be devoted to a detailed analysis of the complete Beethoven sonatas for violin and piano. It arose from the author's desire to pass on to a younger generation more than 60 years' experience as a practising musician and teacher. Professor Rostal addresses himself to professional and amateur musicians alike, to students and to listeners, all of whom will derive pleasure and enlightenment from his words. Each of the ten Sonatas is carefully discussed, the manuscripts and first and later editions meticulously compared. The musician will find technical and interpretative problems approached and solved and the music-lover a helpful listener's guide to these ever-popular masterpieces. Professor Rostal's text is illustrated with over 200 music examples. The frontispieces of the first edition of each of the Sonatas is reproduced, as is a portrait of each of the dedicatees of each work. Max Rostal also addresses the problems facing the editor of music, and questions of dynamics, agogics, ornamentation, orthography, repeats, fingerings and bowings in these Sonatas.
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Sonata; Violin; Piano; Musical interpretation; Vienna (Austria)